A 2009 Social Accounting Matrix (SAM) for Tanzania - Pradesha, Angga; Diao, Xinshen (International Food Policy Research Institute, 2014)
This paper documents a Tanzania Social Accounting Matrix (SAM) for the year 2009. The national SAM is based on newly estimated supply-use tables, national accounts, state budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Tanzania's economy. It separates 58 activities and commodities; labor by different education levels; and households by rural/urban areas as well expenditure quintiles. Labor and household information is drawn from the most recent Tanzania Household Budget Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal tool for economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.